MENINGKATKAN KEMAMPUAN OPERASI PENGURANGAN MELALUI METODE DRILL BAGI ANAK TUNAGRAHITA RINGAN - Elsa Fitri, Damri, Yarmis Hasan (Jurnal Penelitian Pendidikan Khusus, 2013)
This research is motivated by problems in dealing with mild mental retardation children who have problems in solving numbers subtraction operation. Under these conditions, this study aims to prove whether the drill method can improve the ability of reduction surgery for mild mental retardation children in class V SLB Muhammadiyah in Padang. This type of research is the Single Subject Research (SSR) using the AB design. Results for the baseline condition (A) lies in the range of 20% - 30%. After a given intervention (B) the percentage reduction in the ability of the child lies in the range of 40% - 100%. Percentage overlap data obtained at baseline conditions (A) and intervention (B) is 0%. Thus the hypothesis is accepted, that the drill method can improve the ability of mild mental retardation children reduction surgery. Researchers suggest it to teachers and parents to use this method to the maximum drill so children are able to complete the reduction of number operations properly.